2017
DOI: 10.1136/annrheumdis-2017-211989
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose CT detects more progression of bone formation in comparison to conventional radiography in patients with ankylosing spondylitis: results from the SIAS cohort

Abstract: ldCT, covering the whole spine, detects more progression in the form of new and growing syndesmophytes in patients with AS compared with CR, which is limited to the cervical and lumbar spine. Most progression occurred in the thoracic spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 19 publications
(13 reference statements)
3
53
0
3
Order By: Relevance
“…MRI and CT (low‐dose CT if available) should be performed to monitor AS progression only when necessary . Recommended MRI sequence is T1W sequence for structural changes.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI and CT (low‐dose CT if available) should be performed to monitor AS progression only when necessary . Recommended MRI sequence is T1W sequence for structural changes.…”
Section: Recommendationsmentioning
confidence: 99%
“…However, the sensitivity of vertebral inflammation and fat dysplasia on MRI in predicting new syndesmophyte formation remains questionable and still requires further supporting research data . In addition, a recent study has introduced low‐dose CT as an emerging option for monitoring AS progression, as it allows visualization of the whole vertebral column, including the thoracic spine, with higher sensitivity and imaging resolution in detecting new and growing syndesmophytes compared to CR . Low‐dose CT may be considered for a lower cost, relatively lower radiation hazard, fast imaging time, and with advanced sensitivity in monitoring structural changes.…”
Section: Recommendationsmentioning
confidence: 99%
“…In contrast, CT scan methods provide a 360‐degree evaluation of the entire vertebral body, and a better visualization of thoracic spine. Using CT scanning, it has been shown that syndesmophytes develop more commonly at the thoracolumbar junction and thoracic spine, rather than the lumbar spine, offering the potential to detect more patients with abnormalities . In the full‐dose CT scan method, syndesmophyte volume was directly quantified and compared over time using a computer algorithm .…”
Section: Introductionmentioning
confidence: 99%
“…In the full‐dose CT scan method, syndesmophyte volume was directly quantified and compared over time using a computer algorithm . In the low‐dose CT method, a CT syndesmophyte score has been developed to measure the radiographic damage in the entire spine by human readers, with moderate interreader intraclass correlation coefficient for change score . Both CT methods have been shown to be more sensitive to change than the mSASSS , which makes it possible to detect a treatment effect in a clinical trial with fewer participants and/or a shorter study length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation